1999
DOI: 10.1007/s001670050166
|View full text |Cite
|
Sign up to set email alerts
|

Bone tunnel enlargement after anterior cruciate ligament reconstruction with the hamstring autograft and endobutton fixation technique

Abstract: The aim of this study was to describe the contrast-enhanced magnetic resonance imaging (MRI) appearance of bone tunnel enlargement detected on radiography after anterior cruciate ligament (ACL) reconstruction with semitendinosus and gracilis tendon endobutton (STG-endobutton) fixation technique. Fourteen patients with a STG-endobutton ACL reconstruction were examined 3 months (n = 1), 1 year (n = 1) and 2 years (n = 12) postoperatively. An age- and sex-matched group with a bone-patellar tendon-bone (BTB) autog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
124
4
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(136 citation statements)
references
References 20 publications
7
124
4
1
Order By: Relevance
“…We also advocated immediate weight-bearing with a range of movement of 0° to 130°. Our clinical findings support the observation that there is no difference in strain or stress between patellar tendon and four-stranded hamstring grafts in response to cyclic submaximal loading, 26 The importance of minimising the distance between the fixation points to reduce creep when using different grafts has been widely discussed, 24,[27][28][29][30] but no clinical comparisons have been reported between different hamstring fixation techniques. Therefore, it is still not clear if the hamstring graft would provide less laxity if the fixation distance was minimised.…”
Section: Discussionsupporting
confidence: 78%
“…We also advocated immediate weight-bearing with a range of movement of 0° to 130°. Our clinical findings support the observation that there is no difference in strain or stress between patellar tendon and four-stranded hamstring grafts in response to cyclic submaximal loading, 26 The importance of minimising the distance between the fixation points to reduce creep when using different grafts has been widely discussed, 24,[27][28][29][30] but no clinical comparisons have been reported between different hamstring fixation techniques. Therefore, it is still not clear if the hamstring graft would provide less laxity if the fixation distance was minimised.…”
Section: Discussionsupporting
confidence: 78%
“…The longer lever arm on the tibial side causes more mechanical stress Fig. 4 a, clinical results [1][2][3][4]14]. We have one explanation for this result: the bone-tunnel changes are not only circular.…”
Section: Discussionmentioning
confidence: 83%
“…In recent years there have been some reports of bone-tunnel enlargement after ACL reconstruction using autografts [4,5]. Most reports have identified that the bonetunnel enlargement as evaluated with X-rays did not correlate with knee instability [1][2][3][4]14]. On the other hand, a few reports have shown that bone-tunnel enlargement was related to clinical results [7].…”
Section: Introductionmentioning
confidence: 99%
“…CT scanning has been recommended for evaluating the dimensions of the bone tunnels. Compared to plain X-ray films, MSCT has the advantage that it does not depend on geometric factors that may influence measurement, such as a small change in knee positioning or in the exposing distance from the film surface [10,12,13]. We decided to use MSCT images because this technique depicts the real boundaries of the trans-osseous tunnel more exactly.…”
Section: Discussionmentioning
confidence: 99%